Islamic banking services in Malaysia: the extent of customer satisfaction with quality of service - Abdullah, Moha Asri; Abd. Manaf, Noor Hazilah; Ahsan, Kamrul; Azam, Ferdous (2013)
Problem Statement and Objectives of Study: Customer satisfaction on quality of service is an utmost important aspect of any business. The Islamic banking services are not exceptional to this. To examine customer perception, it is important to identify the level of customer satisfaction by measuring the quality of services offered. Such an effort is recognised not only as a significant means for improving services in the banking industry, especially in the Islamic banking industry, but also as an important tool in academic research. Research Methods: In order to realise this research objective, the study utilizes more of a qualitative and descriptive approach than a quantitative one. Other than secondary information, the self-administered questionnaire involving a sample of 178 banking customers from different places in Malaysia is also used as primary data. The customer service quality was analyzed using Mean analysis, Standard deviation and Cronbach’s alpha measurement. Expected Findings: The research draw the relationship between service quality and satisfaction to seek out the best possible results. The study focused on customer satisfaction in areas such as convenient banking locations, accessibility, front desk services, telephone and internet banking services, types of services provided, courtesy of bank employees and provision of other facilities. Significance and Contribution of the Study: The findings of this study, offering an insight into customer perception on the quality of service in the Islamic banking industry, would be beneficial to both academics and practitioners in Malaysia. It is hoped that the findings will assist the banking industry or financial services providers to further improve the quality of their services, provide greater efficiency and be able to better compete with conventional banking services in the marketplace. This study should be a valuable addition to the existing body of knowledge on the quality of service in the Islamic banking industry in Malaysia.